Research on the Effect of Narcissistic Leadership on Employee Job Embeddedness - Wang, Heli; Jiao, Runkai; Li, Feifei (Frontiers in Psychology, 2022)
Narcissistic leadership is the synthesis of narcissistic personality traits and leadership behaviors that are motivated mainly by self-interest needs and arrogant beliefs. Such leadership style has multiple effects on organizations and employees. The amplifying influence of narcissistic leadership on their subordinates has become a hot topic in the field of organizational behavior. Based on the social exchange theory and the resource conservation theory, the current study constructs a chain mediation model of narcissistic leadership affecting employees’ job embeddedness with 405 corporate employees as survey respondents. The results of data analysis show that narcissistic leadership is significantly and negatively related to employees’ job embeddedness; Leader-member exchange (LMX) and perceived insider status not only play a mediating role between narcissistic leadership and job emdeddedness but also play a chain mediating roles in the relationship between narcissistic leadership and job emdeddedness. Our findings deepen the theoretical exploration of narcissistic leadership and help all types of organizations to improve their leadership practices.